Pisolithus sp. tolerance to glyphosate and isoxaflutole in vitro - Fernandes,Mayara Cristina Silva (2014)
The ectomycorrhizal fungi have different tolerance to herbicides and may promote the survival and growth of the eucalypts tree. This study aimed to evaluate the tolerance of Pisolithus sp. isolates to glyphosate and isoxaflutole. The isolates evaluated were D3, D16, D17, Pt24 and UFVJM04. Glyphosate concentrations were: 0, 32, 63, 127 and 254 mg L-1 in liquid medium; 0, 32, 63, 127, 254, 507 and 1014 mg L-1 in solid medium. For isoxaflutole, the concentrations were 0, 295, 589, 1178 and 2355 mg L-1 for both media. Assays were independent for each herbicide and culture medium. The tolerance of isolates depended on the herbicide and its concentration in each type of culture medium. Pt24 was the most tolerant to glyphosate and the UFVJM04 to isoxaflutole. Glyphosate was more toxic to isolates of Pisolithus than isoxaflutole.